2009
DOI: 10.1016/j.jesp.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

From infra-humanization to discrimination: The mediation of symbolic threat needs egalitarian norms

Abstract: a b s t r a c tThis set of studies tests the link between infra-humanization, symbolic threat, and discrimination within normative contexts. In two experiments, manipulating the degree of humanity of a disliked outgroup has an effect upon the discrimination towards it. The infra-humanized outgroup is more discriminated than the humanized one. Also, the perception of symbolic threat plays the role of a justifying factor for discrimination, and mediates the relationship between degrees of humanity and discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(142 citation statements)
references
References 31 publications
7
118
0
14
Order By: Relevance
“…Whereas ''Infra-humanization is not linked to things that people can loose [sic] or gain (money, jobs)'' (Leyens & Demoulin, 2009, p. 212), symbolic threats are conceptually relevant to infrahumanization because they emphasize intergroup differences in characteristics considered unique to humans (e.g., religion, language, culture, and morality, see also Leyens & Demoulin, 2009). In research by Pereira, Vala, and Leyens (2009), manipulations of outgroup infra-humanization increased perceptions of symbolic threat posed by that group. As noted by Simonton (1982), the manipulation of one variable to demonstrate causal effects on the other does not preclude the reverse pattern of causality.…”
Section: Moderated Mediationmentioning
confidence: 98%
“…Whereas ''Infra-humanization is not linked to things that people can loose [sic] or gain (money, jobs)'' (Leyens & Demoulin, 2009, p. 212), symbolic threats are conceptually relevant to infrahumanization because they emphasize intergroup differences in characteristics considered unique to humans (e.g., religion, language, culture, and morality, see also Leyens & Demoulin, 2009). In research by Pereira, Vala, and Leyens (2009), manipulations of outgroup infra-humanization increased perceptions of symbolic threat posed by that group. As noted by Simonton (1982), the manipulation of one variable to demonstrate causal effects on the other does not preclude the reverse pattern of causality.…”
Section: Moderated Mediationmentioning
confidence: 98%
“…Power (Miranda, Vaes, et al, 2010) . Outgroup threat (Castano & Giner-Sorola, 2006;Cehajic et al, 2009;Cuddy et al, 2007;Delgado et al, 2009;Pereira et al, 2009;Tam et al, 2007;Zebel et al, 2008) . Social dominance orientation (Esses et al, 2008;Hodson & Costello, 2007;Leidner et al, 2010) .…”
Section: Moderators Of Outgroup Dehumanisationmentioning
confidence: 99%
“…Manipulating the humanity of a disliked outgroup, Pereira, Vala, and Leyens (2009) showed that people were more willing to discriminate against a less human outgroup. Moreover, perceptions of symbolic threat were shown to mediate this relationship in such a way that symbolic threat justified the discrimination of the outgroup.…”
Section: Vaes Et Almentioning
confidence: 99%
“…Os estudos sobre o essencialismo psicológico têm mostrado que as teorias implícitas que as pessoas mantêm sobre a natureza dos grupos sociais são fatores centrais para compreendermos as tensões intergrupais (Haslam, Bastian, & Bissett, 2004;Leyens et al, 2000;Pereira, Vala, & Leyens, 2009). De acordo com Allport (1954), as pessoas tendem a acreditar que tanto os objetos naturais como os fatos sociais possuem um conjunto fixo e imutável de atributos, ou essências, que definem a natureza desses objetos e fatos.…”
Section: Representações Sobre a Natureza Dos Grupos Sociais E Preconcunclassified